2008
DOI: 10.1520/jai101118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Approach of Irradiation Defects Recovery in Zirconium Alloys: Impact of an Applied Stress

Abstract: During neutron irradiation, both interstitial and vacancy loops are formed in high concentration in zirconium alloys. Due to this high density of loops, the material is considerably hardened, but the recovery of the radiation damage during a heat treatment leads to a progressive softening of the irradiated material. The recovery of the radiation induced hardening has been investigated using microhardness tests. Transmission electron microscopy (TEM) observations performed on irradiated foils have also shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The main risk of rupture at high temperature is due to cladding creep under the internal pressure of fission gases and the temperature due to residual power of the fuel [1]. During post-irradiation creep, the cladding is subjected to heat treatments combined with an applied stress [2] that can affect the irradiation induced microstructure as well as the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main risk of rupture at high temperature is due to cladding creep under the internal pressure of fission gases and the temperature due to residual power of the fuel [1]. During post-irradiation creep, the cladding is subjected to heat treatments combined with an applied stress [2] that can affect the irradiation induced microstructure as well as the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of complex coupling that can arise between thermal recovery and deformation, the understanding of the post-irradiation creep behaviour requires also the study of the creep deformation mechanisms as it has been done elsewhere [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sugiyama et al [3] results indicated that 60% and 85% of the cladding section was at a temperature lower than 350°C and 480°C respectively at cladding fracture. In laboratory tests that aimed at studying RIA conditions should therefore take into account the temperature level as it affects the material mechanical and thermal behavior [7] and the fracture process [10][11][12], the quantity of dissolved hydrides [13] and the extent of the irradiation recovery [14]. The temperature gradient in the cladding wall is likely one of the thermomechanical loading conditions that is most difficult to reproduce experimentally.…”
Section: Temperaturementioning
confidence: 99%
“…The increase in flow stress due to hai loop formation by irradiation generally results in the activation of slip on the basal ({0 0 0 1}) and pyramidal (f1 0 1 1g or f1 0 1 2g) planes [1][2][3][13][14][15]. The other type of loop formed from irradiation damage of zirconium alloys is a vacancy hci loop with a Burgers vector b hci ¼ 1 2 h0 0 0 1i that are formed on the basal planes ({0 0 0 1}) [1,2,6,[9][10][11][12][13][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Since the processes of loop nucleation and change in precipitate structure are believed to be interrelated and are primarily driven by solid-state diffusion, there is a strong dependence of irradiation temperature and flux on these processes that strongly influence the irradiation hardening of Zircaloy [1][2][3][4][5][6][34][35][36][37][38][39][40][41][42][43][44][45]. Irradiation of Zircaloy at higher temperatures (326-450°C) have generally been reported to result in nominally 10-60% less irradiation hardening (Dr) than for irradiation at lower temperatures of 260-326°C [5,6,44,45].…”
Section: Introductionmentioning
confidence: 99%